Guinea-Bissau : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Guinea-Bissau. (International Monetary Fund, 2021)
Guinea Bissau is a fragile state with a long history of political instability. Poverty is high with about 67 percent of the population living below the poverty line of USD 1.90 per day. The economy relies heavily on the production and exports of unprocessed cashew nuts, making most households highly vulnerable to cashew nut price shocks and climate change risks.